INVESTIGATION THE EFFECT OF POTASIUM CARBONATE SOLUTIONS ON DRYING OF SULTANA GRAPES - Ismail, Osman (YILDIZ TECHNICAL UNIV, 2005)
Preserving of foods by drying has became an important subject in food industry. The aim of this work was to determine the effect of various pretreatments on the drying rate and quality of product in drying operation of Sultana grapes. Drying was done in a horizontal air flow drier. The air flow rate in the drier was set to 1,5 m/s. Potassium carbonate solutions for pretreatment of grapes was used for drying. Grapes which are plunged into two solutions was dried in air atmosphere at 60 - 70 degrees C. We also dried grapes with air at 60 and 70 degrees C without pretreatment with any solution in order to compare the drying time. The weight of samples were recorded during drying at every 15-20 minutes until constant weight. These values were used in drawing the drying curves. It is observed that being dried grapes pretreated with 5% K2CO3 - 0,5 % olive oil solutions dried faster. Colour analysis of grapes were done and the best results were obtained in grapes which were pretreated with 5% K2CO3 - 0,5 % olive oil solutions.
Keywords: Drying; Grape; Pretreatment solution; Engineering